A study of vaccination status, weights and birthplace of children aged 12 to 23 months in the Mosvold Health Ward of KwaZulu - Buchmann, Eckhart Johannes (My University, 1992)
The objective of the research reported in this thesis was to describe the vaccination coverage of children aged 12 to 23 months in the Mosvold Health Ward of northern Kwa-Zulu. The Expanded Programme on Immunisation cluster sample technique was used. Simultaneous measurements of the children's weights and arm circumferences were done, and their birthplaces noted. Vaccination coverage rates were generally low; 74 to 83 per cent of the children had had BCG, 47 to 56 per cent had had three doses of DPT, 48 to 57 per cent had had three doses of polio and 47 to 56 per cent had had one dose of measles vaccine. Forty-eight per cent of the children had been born at home. Fifteen per cent had weights which Were more than two standard deviations below the median weight-for-age according to NCHS curves, 11 per cent had arm circumferences of 13,5 centimetres or less. The results are compared with other findings from else Where in southern Africa. Relevant literature on vaccination coverage improvement and the measurement thereof, is reviewed. Recommendations are made for increasing coverage rates in the Mosvold Health Ward) •
A dissertation submitted to the Faculty of Medicine, University df the Witwatersrand in fulfilment of the requirements for the degree of Master of Science in Medicine Johannesburg 1992.
Keywords: Vaccination--in infancy & childhood; Immunization--in infancy & childhood